Effects of a complex strength-training program on athletic performance of junior female handball players - Hammami, M.; Gaamouri, N.; Aloui, G.; Shephard, R. J.; Chelly, M. s. (International Journal of Sports Physiology and Performance, 2019)
Purpose: To analyze the effects of complex strength training on explosive muscle performance of junior female handball players. Methods: Subjects were arbitrarily divided between an experimental group (n = 14) and a control group (n = 14). Training sessions and matches were performed together, but during the 10-wk intervention, the experimental group replaced part of the regular regimen with complex strength training. Measures assessed in both groups before and after the intervention included running times over 5, 10, 20, and 30 m; change-of-direction tests (T-half agility test and modified Illinois test); repeated shuttle sprint ability and repeated change-of-direction tests; jumping (squat, countermovement, countermovement with aimed arms, and 5-jump test); static and dynamic balance; back-extensor strength; and 1-repetition-maximum half-squat. Results: The intervention yielded increases in sprint (10 m 11.7%), change-of-direction performance (T-half 5.1%, modified Illinois 4.2%), jumping (squat P < .01, 19%; countermovement P < .01, 20.3%; countermovement aimed arms P < .01, 19.3%; 5-jump P < .05, 15.2%), and 1 of 4 repeated-sprint scores (best time P < .05, 5.9%). However, repeated-sprint T-test and balance scores were unchanged. Conclusion: Complex strength training develops abilities important to handball performance.